2011
DOI: 10.3899/jrheum.110697
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Blockade Differentially Affects Innate Inflammatory and Th17 Cytokines in Rheumatoid Arthritis

Abstract: Multiple inflammatory pathways contribute to persistent chronic inflammation in RA. In contrast to nonresponders, etanercept therapy modulated serum cytokine levels and caused a marked decrease of IL-6 levels in responders. IL-21 might be involved in the regulation of autoantibody production in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…Other groups have reported that ETN treatment reduces serum IL-6 [12][13][14], but there has been no direct comparison of these two TNF inhibitors in terms of cytokine profiles and clinical responses. We performed longitudinal measurements of serum proinflammatory cytokines in biologics-naïve RA patients, and analyzed the relationship between cytokine profile and clinical effectiveness.…”
Section: Introductionmentioning
confidence: 95%
“…Other groups have reported that ETN treatment reduces serum IL-6 [12][13][14], but there has been no direct comparison of these two TNF inhibitors in terms of cytokine profiles and clinical responses. We performed longitudinal measurements of serum proinflammatory cytokines in biologics-naïve RA patients, and analyzed the relationship between cytokine profile and clinical effectiveness.…”
Section: Introductionmentioning
confidence: 95%
“…At 24 weeks of treatment, serum samples of etanercept (also known as Enbrel, TNF binding protein) plus methotrexate responders had decreased IL-6 whereas increased IL-32 and IL-21. However, there were no differences in cytokine levels in non-responders (18). Pro-inflammatory cytokines contribute to persistent in chronic inflammation of RA and Etanercept therapy regulates level of serum cytokines.…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 84%
“…Both etanercept and adalimumab have been approved by the U.S. Food and Drug Administration (FDA) for human use to prevent inflammatory processes in RA. In RA patients treated with TNF-α inhibitors, serum Th17-related cytokines decreased significantly in parallel with clinical remission in the responders, whereas increased percentage of Th17 cell and elevating related cytokine levels were found in non-responders [6, 7]. However, mechanisms of how these TNF-α inhibitors suppress cytokine production, especially the immunomodulatory effects on Th17 cells, are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%